Fabry's disease: New concepts about its natural history, evolution and treatment, in relation to the findings of the Fabry Registry (2009)
Fabry disease is an inherited lysosomal storage disease caused by deficient activity of the lysosomal enzyme, ?-galactosidase A . Currently, enzyme replacement therapy (ERT) is the specific treatment and it is demonstrated that the early use of it modifies the natural history of the disease. The Fabry Registry is a global, observational, and voluntary program designed to collect clinical data related to the onset, progression, and treatment of Fabry disease. Objective: To assess the natural history, evolution and treatment of Fabry disease. Material and methods: Results: The first symptoms started during childhood with onset occurring at 6 years old in boys and 9 in girls. The average age of diagnosis was at 25 and 32 in male and female respectively. Women involvement was more frequent than previously thought. The average age of the first stroke was at 39 years old in males and 45.7 in females. Conclusion: This analysis of the characteristics of the disease contributes to the growing evidence that Fabry disease starts at childhood, affects both genders and requires a multidisciplinary follow up. An improvement in the knowledge of the natural history of the disorder will get a better rate of suspiciousness in the medical community and an earlier diagnosis and treatment.